The Impact of Trade Policies on Economic Growth in Tanzania - Chindengwike, James (TALENTA PUBLISHER UNIVERSITAS SUMATERA UTARA, 2024)
Effective trade policy is very important to support economic growth. This study's main goal is to evaluate how trade policies affect Tanzania's economic expansion. In this study, quantitative research techniques and a time series research design were used. The study's population consists of economic data spanning the years 1990 to 2020. The analysis examined thirty observations, or annual data, from two trustworthy sources: The World Bank and the International Monetary Fund (IMF). The study's findings indicate that, because the qualities are connected with growth, trade policy influences Tanzania's economic growth. The study comes to the conclusion that trade adjustments in these important sectors gave preference to ineffective operations over productive ones in order to support infrastructure, health, education, and agriculture, the government needs manage its resources well. It should also specify exactly which laws and rules need to be followed in order to implement national policies.